A Long-run Macroeconomic Model of the Austrian Economy (A-LMM). Model Documentation and Simulations - Josef Baumgartner; Helmut Hofer; Serguei Kaniovski; Ulrich Schuh; Thomas Url (Austrian Institute of Economic Research (WIFO), 2004)
In this paper we develop a long run macroeconomic model for Austria to simulate the effects of aging on employment, output growth, and the solvency of the social security system. By disaggregating the population into six age cohorts and modelling sex specific participation rates for each cohort, we are able to account for the future demographic trends. Apart from a baseline scenario, we perform six alternative simulations that highlight the effects of aging from different perspectives. These include two population projections with high life expectancy and with low fertility, a dynamic activity rate scenario, two scenarios with a stable fiscal balance of social security and an alternative pension indexation, and a scenario with higher productivity growth.
Keywords: C6; E2; O4; 330; Economic growth; aging; Austria; Beschäftigungseffekt; Wirtschaftswachstum; Gesundheitsfinanzierung; Wachstumstheorie; Makroökonometrie; Makroökonomik; Österreich; Alternde Bevölkerung